Pre-Hospital Anesthesia Handbook - Griffiths, Andrew; Lowes, Tim.; Henning, Jeremy; SpringerLink (Online service) (London : Springer London : Imprint: Springer, 2010)
The safe and swift establishment of a secure airway is crucial in the pre-hospital situation, and many pre-hospital systems have developed standard operating procedures that involve inducing anesthesia for airway control. Developed from the manual for a two-day course on the introduction to pre-hospital anesthesia given by the Great North Air Ambulance Service, the Pre-Hospital Anesthesia Handbook details the procedures, drugs and algorithms used by the expert crews of the Great North Air Ambulance. Authored by authorities in both the clinical application and the academic research aspects of pre-hospital anesthesia, it provides a focused, evidence-based foundation for any practitioner who wishes to learn this potentially life-saving procedure.
Indications and Decision Making -- Pre-Hospital Rapid Sequence Intubation -- Post-intubation Management -- Equipment and Minimum Monitoring Standards -- Drugs and Sedation -- Special Circumstances -- Complications and Adverse Events.
Keywords: Medicine; Anesthesiology; Emergency medicine; Critical care medicine; Medicine & Public Health; Anesthesiology; Emergency Medicine; Intensive / Critical Care Medicine